E-Banking Adoption and Business Performance of SMES in Uganda a Case Study of Kabale Municipality. - Nakazibwe, Martha (Kabale University, 2023)
This research was conducted in Kabale municipality Kabale District to examine the effect of e-banking adoption on business performance of SMEs. The predictor variables under study were Level of E-banking, Level of Business performance and relationship between variables while business performance of SMEs was the outcome variable. The study followed a cross sectional survey. Data from 109 respondents was collected and analyzed quantitatively complemented with qualitative analysis. Since descriptive analysis entailed description of a single variable and its attributes, frequency tables were used to present the data. At the bivariate level, a Pearson correlation matrix was conducted to ascertain the relationships between the predictor variables and the dependent variable. A linear regression model was used to fit the data. Research findings from the regression model show that level of e-banking adoption (R= r=668**), level of business performance (R=456 and relationship between variables (R=549) have a positive significance. The main conclusion drawn from this research is that level of e-banking, level of business performance of SMEs and the relationship between variables. The study therefore recommends that the report suggests that in order to reduce the financial risks associated with moving money around, all SMEs in Kabale Municipality should switch to electronic banking